Effect of HIF-1α on VEGF-C Induced Lymphangiogenesis and Lymph Nodes Metastases of Pancreatic Cancer - 陶京 李弢 李凯 熊炯炘 杨智勇 吴河水 王春友 (Journal of Huazhong University of Science and Technology. Medical sciences, 2006)
The effect of hypoxia inducible factor-1 α （HIF-1 α） on vascular endothelial growth factor C （VEGF-C） and the correlation between HIF- 1 α and lymphangiogenesis and lymph nodes metastases （LNM） in pancreatic cancer were investigated. Immunohistochemical SP method was used to detect the protein expression of HIF-1 α and VEGF-C, and Lymphatic vessel density （LVD） was determined by stain of VEGFR-3, collagen type IV in 75 pancreatic head cancers from regional pancreatectomy （RP） during Dec. 2001 to Dec. 2003. The relationship between HIF-1α and VEGF-C, lymphangiogenesis, LNM was analyzed statistically. The results showed that the positive expression rate of HIF-1α and VEGF-C in pancreatic cancer tissues was 48.00 % （36/75） and 65.33 % （49/75） respectively. In positive group of HIF-1α, the positive rate of VEGF-C and LVD, and LVD rate was 80.56 % （29/36）, 13.22±3.76 and 88.89 % （32/36） respectively, and in negative group of HIF-10t, positive rate of VEGF-C and LVD was 51.28 % （20/39）, 5.98±2.17 and 66.67 % （26/39） respectively （P〈0.01 or P〈0.05）. It was suggested that HIF-1α could promote the expression of VEGF-C, lymphangiogenesis and LNM in pancreatic cancer.